Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1126/scitranslmed.aaf1629
|View full text |Cite
|
Sign up to set email alerts
|

Nigral dopaminergic PAK4 prevents neurodegeneration in rat models of Parkinson’s disease

Abstract: Parkinson's disease (PD) is characterized by progressive loss of dopaminergic (DA) neurons in the substantia nigra. No neuroprotective treatments have successfully prevented the progression of this disease. We report that p21-activated kinase 4 (PAK4) is a key survival factor for DA neurons. We observed PAK4 immunoreactivity in rat and human DA neurons in brain tissue, but not in microglia or astrocytes. PAK4 activity was markedly decreased in postmortem brain tissue from PD patients and in rodent models of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 65 publications
1
57
2
Order By: Relevance
“…Prosurvival factors with increased levels in ocular motor neurons were for instance (i) the CDKN1A activated kinases Pak6 and Pak4. Pak4 prevents caspase activation and thus apoptosis (Gnesutta and Minden 2003;Gnesutta et al 2001) and encouragingly, its neuroprotective function was recently demonstrated in a rat model of Parkinson's disease (Won et al 2016). (ii) The mitochondrial aldehyde dehydrogenase Aldh4a1, which can safeguard cells from oxidative stress (Yoon et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Prosurvival factors with increased levels in ocular motor neurons were for instance (i) the CDKN1A activated kinases Pak6 and Pak4. Pak4 prevents caspase activation and thus apoptosis (Gnesutta and Minden 2003;Gnesutta et al 2001) and encouragingly, its neuroprotective function was recently demonstrated in a rat model of Parkinson's disease (Won et al 2016). (ii) The mitochondrial aldehyde dehydrogenase Aldh4a1, which can safeguard cells from oxidative stress (Yoon et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Phosphorylation at Ser133 is required for CREBs to bind to CREB-binding proteins (CBPs) [35]; however, PAK4mediated CREB activation is independent of its phosphorylation at Ser133. Rather, PAK4 activates CREB by phosphorylating CREB-regulated transcriptional cofactor 1 (CRTC1), a coactivator of CREB [36]. The phosphorylation status and phosphorylation site of CREB3L4 need to be further studied in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CREB mediates neuroprotection mainly via its downstream genes, such as peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1a) [21], brain-derived neurotrophic factor (BDNF) [22] and B-cell lymphoma 2 (Bcl-2) [23]. Deregulation of CREB signaling is associated with several neurodegenerative diseases, for instance, Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD) and ALS [22,[24][25][26]. Restoring CREB activity rescues defects in dendrite morphogenesis in TDP-43 misregulated neurons [27].…”
Section: Introductionmentioning
confidence: 99%
“…Group II PAKs contribute to a wide range of intracellular processes including cytoskeletal dynamics, cell growth, tumorigenesis, neuronal dysfunction and cell survival [30][31][32][33][34]. Studies on PAK4 have revealed its pivotal role in cytoskeletal remodeling, neuronal development, axonal outgrowth and neuronal survival [24,35,36]. PAK4 knockout mice display dramatic defects in the heart and nervous system, with striking abnormalities observed in axonal outgrowth and neural tube formation [36].…”
Section: Introductionmentioning
confidence: 99%